Factor Analysis about Exclusive Breastfeeding Achievement Level among Mothers Who Provide Breastmilk to Their Children - Tiyas Kusumaningrum; Catur Puji Lestari; Agus Sulistyono (Universitas Airlangga, 2010)
Introduction: The number of mother who breastfeed their babies exclusively in Indonesia is low. It caused by many factors such as high intensity of formula milk advertisement, lack of awareness about the importance of breastfeeding, working mother, social culture, family support and the role of health care provider. The purpose of this research was to analyze factors related with successfulness level of exclusive breastfeeding.Methods: Design used in this research was analytic retrospective. The population were all mothers at Pacarkeling Public Health Center area. Sample obtained through purposive sampling. Total sample was 61 respondents. Independent variables were knowledge, information and promotion, family support, social cultural, role of health provider, work/occupation, education and breast physiology anatomy. The dependent variable was exclusive breastfeeding.Results: The result indicated that exclusive breastfeeding achievement level was related with information and promotion (r = 0.271), family support (r = 373), health care provider role (r = 231), mother occupation (r = 251), anatomy and physiology of breast (r = 293), while the knowledge (r = 108), social cultural (r = 180) and education (r = 093) not significantly related.ConclusionIn conclusion, there was a positive correlation between information and promotion, family support, health care provider role, mother’s occupation, anatomy and physiology of breast with successfulness level of exclusive breastfeeding. While the knowledge, social cultural and education did not indicate significant result. Therefore it is suggested to increase the quantity and quality of information and promotion about exclusive breastfeeding to the society, health care provider and pregnant and breastfeeding mother.